Македонското знаме на страниците на Флагмастер - Macedonian flag on the pages of Flagmaster - Jonovski, Jovan (Македонски хералд - Macedonian Herald, 2021)
Flagmaster, the journal of the Flag Institute from London, has eight articles about the Macedonian flag, four about the adoption of the flag of 1992 and possible alternatives, and two regarding the flag change of 1995. They gives six illustrations of flags of which only one could be considered acceptable, the one of the new flag. The three offered images of the 1992 flags were either not right or not close enough. This article presents the information and drawings from these issues and gives analysis and explanation of some of the background connected with these two processes.